Dissociating hyper and hypoself biases to a core self-representation. (September 2015) - Sui, Jie; Enock, Florence; Ralph, Jane; Humphreys, Glyn W.
Abstract: Biases to favour self-related information over information related to other people have been demonstrated across a range of both high- and low-level tasks, but it is unclear whether these tasks 'tap' the same types of self representation. Here we assess results from two patients with damage primarily to (i) left ventro-medial prefrontal (vmPFC) cortex and the insula (patient SC), and (ii) temporo-parietal (TP) cortex (patient RR). We report evidence from both low-level perceptual matching tasks and episodic memory showing that SC has a hypoself bias across the tasks. RR in contrast had a hyperself bias confined to perceptual matching. Both patients also showed hypobias effects for reward. We argue that the different brain lesions compromise (i) the use of a core self-representation which modulates both perceptual and memorial levels of processing (the vmPFC), and (ii) attentional responses to social cues (the TP cortex), and, furthermore, these effects can dissociate from those of reward and general effects of brain lesion and/or impaired executive control. We suggest that the vmPFC is critical for access to a core self-representation while TP damage can reduce top-down control of attention to salient stimuli and exaggerates the effects of strong (self-related) attentional signals.